Heart Rate Variability as a Prognostic Factor for Cancer Survival – A Systematic Review - Kloter, Evelyne; Barrueto, Katja; Klein, Sabine D.; Scholkmann, Felix; Wolf, Ursula (Frontiers in Physiology, 2018)
An increasing cancer incidence affecting any age and social class is putting serious strain on populations and health care systems around the world. This systematic literature search aims i) to examine the correlation of heart rate variability (HRV) and cancer patients’ prognosis, ii) to examine the relationship of HRV and clinicopathological features, and iii) to compare HRV between different patient groups, and between patient and control groups. We conducted a systematic literature review following the PRISMA Statement. We searched the PubMed and EMBASE databases for publications released by December 2017. The search terms were: “cancer” AND “heart rate variability” AND “human” NOT “animal” NOT “review”. A total of 19 studies were finally included in this review. Most publications were high-quality observational studies. The studies showed that higher HRV correlated positively with patients’ progression of disease and outcome. Thus, we conclude that individuals with higher HRV and advanced coping mechanisms seem to have a better prognosis in cancer progression. HRV appears to be a useful aspect to access the general health status of cancer patients.